Tall building design steel, concrete, and composite systems - Taranath, Bungale S. (CRC Press, 2017)
The book explains loads and load combinations typically used in building design, explores methods for determining design wind loads using the provisions of ASCE 7-10, and examines wind tunnel procedures.